Mudança organizacional em um sistema complexo: as lições do caso da incorporação do BNH pela CEF - Alcântara Júnior, Otávio de Castro (2006)
The present study examines the impacts of the union of the National Habitation Bank with the Federal Caixa Econômica in 1986, emphasizing structural aspects, dealing with the origin of the organizations involved, the context in which it happened, the structural changes, the objectives and the purposes that have been aimed by the Federal Caixa Econômica since 1986, as well as the impact produced by the change over the remaining employees from the National Habitation Bank. The method used was based on the qualitative approach, and the investigative technique was centered on case studies in which biographic data, documental study and interviews are used. The results show that the objectives and purposes performed by the National Habitation Bank, in the scope of habitation and urban development that, with its extinction, started to be carried out by the Federal Caixa Econômica, kept the general characteristics of what was executed by National Habitation Bank, but with a great evolution of the programs used, with the generation of new programs and with a bigger connection of the resources to be applied in the sector with the sources of funds, proving that even with the differences existents between the two organizations before the union of the National Habitation Bank and the Federal Caixa Econômica, it was possible to keep the know-how, and even develop it. We hope that this study can help the discussions about processes like the ones of absorption, acquisition and union of organizations in what refers to structure and roles of the organizations.